Ngeteh Cafe / Nur Aisha Mohd Yusoff ... [et al.] - Mohd Yusoff, Nur Aisha; Mamat, Amira; Torji, Fatin Amirah; Mohd Mohamadiah, Nabila Hanim; Nik Mohd Fakhri, Nik Nur Fadhilah; Mohamad, Nur Adreana Syahila; Mohamad, Nur Amiera Shahierah; Mohd Usooff, Nur Syamimi (2022)
In order for us to complete this subject which is Principles of Entrepreneurship (ENT530), we have to complete this assignment that has already been assigned to us. Under this group assignment, we need to set up a company and point out the details of what our company wants to accomplish with our product or services. Hence, the name of the company that we choose is Ngeteh Cafĕ and our nature of product is desserts and pastries. As we all know, nowadays a cafĕ is one of the most popular hangout spots in society because the ambience is pleasant to chill on. Ngeteh Cafĕ was founded with the objectives of providing complete customer satisfaction by maximising product quality and hygiene at an accessible price, as well as providing friendly and warm cafe service that ensures our guests have the best experience and memories possible when visiting our cafe. Ngeteh Cafĕ is a partnership enterprise with eight partners in Kota Bharu, Kelantan, located on Jalan Abdul Kabir Adabi. It is overseen by a team of eight employees, led by general manager Nik Nur Eadhilah binti Nik Mohd Eakhri. Ngeteh Cafĕ finances their business with an RM35650 personal commitment from the partners.